Policies to create and destroy human capital in Europe - James Joseph Heckman; Bas Jacobs (Institute for the Study of Labor (IZA), 2009)
Trends in skill bias and greater turbulence in modern labor markets put wages and employment prospects of unskilled workers under pressure. Weak incentives to utilize and maintain skills over the life-cycle become manifest with the ageing of the population. Reinvention of human capital policies is required to avoid increasing welfare state dependency among the unskilled and to reduce inefficiencies in human capital formation. Policy makers should acknowledge strong dynamic complementarities in skill formation. Investments in the human capital of children should expand relative to investment in older workers. There is no trade-off between equity and efficiency at early ages of human development but there is a substantial trade-off at later ages. Later remediation of skill deficits acquired in early years is often ineffective. Active labor market and training policies should therefore be reformulated. Skill formation is impaired when the returns to skill formation are low due to low skill use and insufficient skill maintenance later on in life. High marginal tax rates and generous benefit systems reduce labor force participation rates and hours worked and thereby lower the utilization rate of human capital. Tax-benefit systems should be reconsidered as they increasingly redistribute resources from outsiders to insiders in labor markets which is both distortionary and inequitable. Early retirement and pension schemes should be made actuarially fairer as they entail strong incentives to retire early and human capital is thus written off too quickly.
Keywords: H2; H5; I2; I3; J2; J3; 330; Skill formation; human capital; labor supply; retirement; training; dynamic complementarity; inequality; returns to education; (non)cognitive skills; family policy; training policy; active labor market policy; tax policy; benefit systems; pension policy; welfare state; Qualifikation; Bildungsinvestition; Bildungspolitik; Arbeitsmarktpolitik; Sozialstaat; Ökonomischer Anreiz; Bildungsverhalten; Europa